Combating Nuclear Terrorism Threats Through Development of Evolving Nuclear Security Regime - Baraedi, Tumelo (UNWE Yearbook, 2024)
Nuclear terrorism refers to the unauthorized use or attempted use of nuclear explosive devices (e.g., Improvised Nuclear Devices (IND’s), and radioactive ones (e.g., Radiation Dispersal Devices (RDD’s) or Radiation Emitting Devices (RED’s)), as well as attacks/attempted attacks on nuclear/radiation facilities. The main objective is to review some major challenges encountered by having an evolving nuclear security regime, with the main focus being on nuclear terrorism. The paper seeks to suggest recommendations that can be used in reducing the threat of nuclear terrorism and maintaining an effective nuclear security regime which can be used in combating nuclear terrorism. The research was conducted through a literature review of international instruments such as IAEA publications (e.g. IAEA NSS No. 6) on maintaining a sustainable nuclear security regime and an analysis of the indicators that could play a key role in maintaining these. The survey was also conducted on both radiation workers and the public.
Keywords: Combating nuclear terrorism; Illicit trafficking; Nuclear security regime